Caring as the essence and science of Nursing and health care - Watson, Jean (O Mundo da Saúde, 2009)
Human Caring is part of the human condition and a way of Being Human. Caring is found throughout time. Moreover, the notion of ‘caring’ in nursing has been a given throughout its history. In the past 3 decades or so, professional human caring has been increasingly acknowledged as the essence and core of professional nursing. This focus is evident in nursing practice, nursing theories, nursing curricula, and nursing’s philosophical and ethical perspective toward humanity and patient caring relationships. In this paper, I present the main tenets of works by means of which I have posited Caring as the disciplinary foundation for nursing and have put forward Caring Science as an evolved view of nursing and human sciences (WATSON,1979, 1985, 1999, 2005, 2008).